2020
DOI: 10.3390/s20041190
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Filtering for Frequency Identification of Bridges Using Smartphones in Passing Vehicles: Fundamental Developments and Laboratory Verifications

Abstract: This paper puts forward a novel methodology of employing inverse filtering technique to extract bridge features from acceleration signals recorded on passing vehicles using smartphones. Since the vibration of a vehicle moving on a bridge will be affected by various features related to the vehicle, such as suspension and speed, this study focuses on filtering out these effects to extract bridge frequencies. Hence, an inverse filter is designed by employing the spectrum of vibration data of the vehicle when movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Yang et al 31 showed that when one considers the influence of roughness, vehicle responses dominate the acceleration spectrum and overshadows the bridge frequency components. However, recent studies based on Hilbert transform and inverse filtering show promising result in terms of extracting the bridge frequencies 32,33 . Current techniques to deal with the roughness problem are based on subtracting the signal from two adjacent axles which eliminate the effect of road roughness 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 31 showed that when one considers the influence of roughness, vehicle responses dominate the acceleration spectrum and overshadows the bridge frequency components. However, recent studies based on Hilbert transform and inverse filtering show promising result in terms of extracting the bridge frequencies 32,33 . Current techniques to deal with the roughness problem are based on subtracting the signal from two adjacent axles which eliminate the effect of road roughness 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…More research followed the pioneers above; numerous researchers performed proof-of-concept tests to retrieve modal frequency data from moving vehicles instrumented with smartphones [ 122 , 123 , 124 ]. Likewise, more advanced techniques were developed, such as an inverse filtering approach for frequency identification [ 125 ] and more complex drive-by modal analyses [ 126 ] and clock-asynchronous data [ 127 ]. Concerning bridges, the drive-by data encapsulates the mechanical features of the bridge, as well as the vehicle, and the interaction with each other.…”
Section: Drive-by Smartphone Sensing For Bridge Monitoringmentioning
confidence: 99%
“…It was found that high vehicle damping [20], the increase of vehicle body mass [21], and heavy vehicles [22] could help suppress the vehicle frequency and the efect of road roughness, making the bridge's fundamental frequency highlighted. To eliminate the efects of the vehicle's self-vibration parameters, Shirzad-Ghaleroudkhani and Gül [23] tried to drive the vehicle of the bridge at frst and then on the bridge to inversely flter out the vehicle's frequencies. To overcome the inverse efects of high vehicle speed, wavelet transform, and Hilbert transform were utilized to increase the frequency resolution of vehicle accelerations [24,25].…”
Section: Introductionmentioning
confidence: 99%